Lechevalieria nigeriaca sp. nov., Isolated From Arid Soil - Camas, M.; Veyisoǧlu, A.; Tatar, D.; Saygın, H.; Çetin, D.; Sazak, A.; Güven, K. (Soc General Microbiology, 2013)
A novel actinobacterium, designated strain NJ2035T, was isolated from soil collected from Abuja, Nigeria and was characterized to determine its taxonomic position. The isolate was found to have chemical and morphological properties associated with members of the genus Lechevalieria. Phylogenetic analyses based on almost-complete 16S rRNA gene sequences indicated that the isolate was closely related to members of the genus Lechevalieria, and was shown to form a distinct phyletic line in the Lechevalieria phylogenetic tree. Strain NJ2035T was most closely related to Lechevalieria roselyniae C81T, Lechevalieria atacamensis C61T and Lechevalieria deserti C68T (98.5% 16S rRNA gene sequence similarity). Sequence similarities with other members of the genus Lechevalieria were less than 98.2 %. The cell wall of the novel strain contained meso-diaminopimelic acid, and galactose, mannose and rhamnose as the diagnostic sugars. The predominant menaquinone was MK-9(H4). The polar lipids detected were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. DNA-DNA relatedness and phenotypic data showed that the novel isolate and L. roselyniae C81T, L. atacamensis C61T and L. deserti C68T belong to distinct genomic species. On the basis of data from this taxonomic study using a polyphasic approach, strain NJ2035T represents a novel species of the genus Lechevalieria, for which the name Lechevalieria nigeriaca sp. nov. is proposed. The type strain is NJ2035T (=DSM 45680T=KCTC 29057T=NRRL B-24881T). © 2013 IUMS.